Legal Innovation for Protection of Victims of Domestic Violence - Yudistira, Febiahwan (Journal of Creativity Student, 2019)
Protection of victims of domestic violence is one of the challenges facing Indonesia. Although national legal instruments have accommodated various forms of victim protection in cases of domestic violence, many obstacles have been encountered, especially with regard to how to restore the rights of women victims from the perspective of the criminal law system. This paper aims to analyze the legal innovation of protection for victims of domestic violence in Indonesia. The method used in this paper is normative juridical which examines various applicable legal rules and norms related to the case.